Phytoplankton diversity as a bioindicator for water quality of siwak bay, Specific Economic Zone (SEZ) Mandalika Central Lombok - Izma Paryantini; Dining Aidil Candri; Lalu Japa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The Mandalika Specific Economic Zone (SEZ) is a potential tourism industry for the province of West Nusa Tenggara, which has recently received very high attention due to the construction of the international MotoGP circuit. The construction of the MotoGP circuit has become an attraction for domestic and foreign tourists and has increased the number of tourists. The increase in tourism activity has negatively impacted the Mandalika SEZ's coastal waters, such as a decrease in water quality, including the water of Siwak Bay. Water quality monitoring can be done by using phytoplankton as a bioindicator. The study of phytoplankton species diversity as a bioindicator of water quality has never been carried out in the Siwak Bay waters. This research was conducted to analyze the status of Siwak Bay waters based on the phytoplankton diversity index. Samplings were carried out based on a purposive sampling method. This research was conducted for three months, from March to June 2023. The study found seven classes, 59 genera, and 127 phytoplankton species. The abundance of phytoplankton in Siwak Bay was 1025,185 ind/L. The highest abundance was the genus of Trichodesmium. The species diversity index was 3,33. Based on the species diversity index, it can be said that the waters of Siwak Bay are not polluted.